Skeletal Muscle Oxygen Saturation (StO2) Measured by Near-Infrared Spectroscopy in the Critically Ill Patients. (21st August 2013) - Mesquida, J.; Gruartmoner, G.; Espinal, C.
Abstract : According to current critical care management guidelines, the overall hemodynamic optimization process seeks to restore macrocirculatory oxygenation, pressure, and flow variables. However, there is increasing evidence demonstrating that, despite normalization of these global parameters, microcirculatory and regional perfusion alterations might occur, and persistence of these alterations has been associated with worse prognosis. Such observations have led to great interest in testing new technologies capable of evaluating the microcirculation. Near-infrared spectroscopy (NIRS) measures tissue oxygen saturation (StO2 ) and has been proposed as a noninvasive system for monitoring regional circulation. The present review aims to summarize the existing evidence on NIRS and its potential clinical utility in different scenarios of critically ill patients.